LIBER Workshop "Microfilming and Digitisation for Preservation" - Cabral, Maria Luisa (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
The Workshop on "Microfilming and Digitisation for Preservation" which is presented here through papers brought forward held at The Hague on 14-15 April 2003 in the Koninklijke Bibliotheek, the National Library of the Netherlands, was the outcome of a long process which started nearly three years ago. Cooperation is a good thing - the right thing, hélas! - in all circumstances of life. For libraries, the European Union has been an elected stage to perform all sorts of alliances. We all have memories of successful partnerships; we all have tried to learn from each others ’projects’ which swept over Europe. This Workshop was the result of our previous cooperative experience, but also of our conviction about library needs. The LIBER Preservation Division together with the Koninklijke Bibliotheek and European Commission on Preservation and Access (ECPA) elaborated a programme based on different inputs and viewpoints which after long discussions via e-mail finally built up a structure. To identify the appropriate speaker, and to guarantee his/her presence was another organizational level not less arduous, though. Sharing the same commitment was decisive to the success of the Workshop.